2017
DOI: 10.1177/1934578x1701200624
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Zingerone on Secretory Group IIA Phospholipase A2

Abstract: The expression of secretory group IIA phospholipase A2 (sPLA2-IIA) has been shown to be elevated in various inflammatory diseases, and lipopolysaccharide (LPS) up-regulates the expression of sPLA2-IIA in human umbilical vein endothelial cells (HUVECs). Zingerone (ZGR), a phenolic alkanone isolated from ginger, has been reported to have various pharmacological activities. Here, we examined the effects of ZRG on the expression and activity of sPLA2-IIA in LPS-activated HUVECs and in mouse models of endotoxemia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Previous reports showed that treatment of cells or mice with ZGR inhibited LPS-induced expression and activity of sPLA2-IIA which contributes to vascular inflammation (16) and ZGR has anti-platelet aggregation activity (17). In those studies, ZGR was used from at 10 μM to 50 μM in human endothelial cells and from at 0.14, 0.36, or 0.72 mg/kg in mice (16, 17). Therefore, in this study, ZGR was also used from 0.07 to 0.72 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports showed that treatment of cells or mice with ZGR inhibited LPS-induced expression and activity of sPLA2-IIA which contributes to vascular inflammation (16) and ZGR has anti-platelet aggregation activity (17). In those studies, ZGR was used from at 10 μM to 50 μM in human endothelial cells and from at 0.14, 0.36, or 0.72 mg/kg in mice (16, 17). Therefore, in this study, ZGR was also used from 0.07 to 0.72 mg/kg.…”
Section: Resultsmentioning
confidence: 99%